Pengaruh Pengembangan Karir, Motivasi Kerja dan Komimetmen Organisasi Terhadap Kinerja Pada PT. Greenspan Packaging System Jakarta - Devia; Pujiati, Herni; Sadipung, Theresia Oktavia; Cahaya, Yohanes Ferry; Ramdan, Amir (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
This research aims to analyze the influence of career development, work motivation, and organizational commitment on the performance of Production Division employees PT. Greenspan Packaging Systems Jakarta. This research uses a quantitative approach, survey methods, and path analysis. The population is made up of employees of the Production Division of PT. Greenspan Packaging System Jakarta, totaling 84 people. With the saturated sampling technique, 84 respondents were obtained. The data were analyzed using Excel and SPSS 25.0. The research results show that: career development has a direct positive and significant effect on organizational commitment of 0.328; work motivation has a direct positive and significant effect on organizational commitment of 0.670; career development has a direct positive and significant effect on performance of 0.481; work motivation has a direct positive and significant effect on performance of 0.268; and organizational commitment has a direct positive and significant effect on the performance of employees of the Production Division of PT. Greenspan Packaging System Jakarta is 0.246.